In vitro evaluation of Spirulina platensis extract incorporated skin cream with its wound healing and antioxidant activities - Seda Gunes; Sedef Tamburaci; Meltem Conk Dalay; Ismet Deliloglu Gurhan (Taylor & Francis Group, 2017)
Context: Algae have gained importance in cosmeceutical product development due to their beneficial effects on skin health and therapeutical value with bioactive compounds. Spirulina platensis Parachas (Phormidiaceae) is renowned as a potential source of high-value chemicals and recently used in skincare products. Objective: This study develops and evaluates skin creams incorporated with bioactive S. platensis extract. Materials and methods: Spirulina platensis was cultivated, the aqueous crude extract was prepared and in vitro cytotoxicity of S. platensis extract in the range of 0.001-1% concentrations for 1, 3 and 7 d on HS2 keratinocyte cells was determined. Crude extracts were incorporated in skin cream formulation at 0.01% (w/w) concentration and in vitro wound healing and genotoxicity studies were performed. Immunohistochemical staining was performed to determine the collagen activity. Results: 0.1% S. platensis extract exhibited higher proliferation activity compared with the control group with 198% of cell viability after 3 d. Skin cream including 1.125% S. platensis crude extract showed enhanced wound healing effect on HS2 keratinocyte cell line and the highest HS2 cell viability % was obtained with this concentration. The micronucleus (MN) assay results indicated that S. platensis extract incorporated creams had no genotoxic effect on human peripheral blood cells. Immunohistochemical analysis showed that collagen 1 immunoreactivity was improved by increased extract concentration and it was strongly positive in cells treated with 1.125% extract incorporated skin cream. Conclusions: The cell viability, wound healing activity and genotoxicity results showed that S. platensis incorporated skin cream could be of potential value in cosmeceutical and biomedical applications.